Ask the Experts: Automation: Part II. (September 2013) - Unknown
Bioanalysis invited a selection of leading researchers to express their views on automation in the bioanalytical laboratory. The topics discussed include the challenges that the modern bioanalyst faces when integrating automation into existing drug development processes, the impact of automation and how they envision the modern bioanalytical laboratory changing in the near future. Their enlightening responses provide a valuable insight into the impact of automation and the future of the constantly evolving bioanalytical laboratory.